ESMO Management and treatment adapted recommendations in the COVID-19 era: Lung cancer. (23rd June 2020) - Passaro, Antonio; Addeo, Alfredo; Von Garnier, Christophe; Blackhall, Fiona; Planchard, David; Felip, Enriqueta; Dziadziuszko, Rafal; de Marinis, Filippo; Reck, Martin; Bouchaab, Hasna; Peters, Solange
Abstract : The COVID-19 pandemic, characterised by a fast and global spread during the first months of 2020, has prompted the development of a structured set of recommendations for cancer care management, to maintain the highest possible standards. Within this framework, it is crucial to ensure no disruption to essential oncological services and guarantee the optimal care. This is a structured proposal for the management of lung cancer, comprising three levels of priorities, namely: tier 1 (high priority), tier 2 (medium priority) and tier 3 (low priority)—defined according to the criteria of the Cancer Care Ontario, Huntsman Cancer Institute and Magnitude of Clinical Benefit Scale. The manuscript emphasises the impact of the COVID-19 pandemic on lung cancer care and reconsiders all steps from diagnosis, staging and treatment. These recommendations should, therefore, serve as guidance for prioritising the different aspects of cancer care to mitigate the possible negative impact of the COVID-19 pandemic on the management of our patients. As the situation is rapidly evolving, practical actions are required to guarantee the best patients' treatment while protecting and respecting their rights, safety and well-being. In this environment, cancer practitioners have great responsibilities: provide timely, appropriate, compassionate and justified cancer care, while protecting themselves and their patients from being infected with COVID-19. In case of shortages, resources must be distributed fairly. Consequently, the following recommendations can be applied with significant nuances, depending on the time and location for their use, considering variable constraints imposed to the health systems. An exceptional flexibility is required from cancer caregivers.